Ideological Cleavage under Open-list Proportional Representation: Parties’ Position toward the 2019 Indonesian Presidential Threshold - Ridho Al-Hamdi (Faculty of Social and Political Sciences, Universitas Gadjah Mada, 2021)
This article examines the ideological position of Indonesia’s political parties in addressing the 2019 presidential threshold under the open-list proportional representation system. The article aims to determine the political cleavage among Indonesian political parties, whether classified into the ideological spectrum or the organisational degree. From a methodological standpoint, it is qualitative research by employing in-depth interviews and online news collection as a data gathering technique. The study’s finding depicts that the ideological cleavage is no longer relevant under the open-list proportional representation system because political parties eventually have pragmatical orientations rather than ideological onsiderations. It can be proven that the position of nationalist secular parties is not merely in the approval side but also in the denial and dilemma sides. Likewise, the position of nationalist Islamist parties can be found on two sides: denial and dilemma. This finding verifies that Indonesia’s ideological contestation is waning and inactive when political parties cope with power issues. On the contrary, the ideology is revived when it deals with religious and tribal affairs.